MODEL PENINGKATAN KINERJA SUMBER DAYA MANUSIA MELALUI KNOWLEDGE SHARING - Ervina Ervina (Jurnal Riset Bisnis Indonesia, 2014)
The objective use of this research us to analyze the influence of communication,trust organizationalculture, performance of human Resour with Knowledge Sharing intervening variabel. These variables, researchers using BPS employees Southeast Sulawesi Province as a sample by distributingquestionnaires 63 people . All of the employee used as responden. The results of this study showedthat communication significant positive effect on knowledge sharing , communication significantpositive effect on the performance of human resources , Trust significant positive effect on knowledgesharing , trust significant positive effect on the performance of human resources , organizationalculture significant positive effect on knowledge sharing , significant positive effect of organizationalculture on the performance of human resources , and knowledge sharing significant positive effecton the performance of human resources .Keywords: Communication , Trust, Organizational Culture ,Knowledge Sharing , and Performanceof Human Resour